Changing demographics and housing typologies: Addressing social and affordable housing in Australia - Zingoni de Baro, Maria Elena; Kraatz, J. (Griffith University, 2018)
This paper will report on current Sustainable Built Environment National Research Centre (SBEnrc) research which aims to identify the strengths and weaknesses of various social procurement approaches for social and affordable community rental housing in Australia. To achieve this, the research team is investigating the three inter-related areas of: demographics and typologies; social procurement; and funding and financing models. This paper will primarily discuss findings of the first of these three areas. An important question being asked is: has the time come to rethink the traditional distinctions between elements of the housing continuum in order for governments and not-for-profits to better engage with the market and institutional investors? In doing this, and to ensure access to safe and secure housing when needed, we need to: (i) address the types of housing being provided across the spectrum; (ii) better understand the changing nature, needs and demographics of each cohort; and (iii) diversify our housing responses, seeking innovative and perhaps informal approaches providing housing which respond to the various needs of different cohorts. Early findings around the demographic and typological theme are showing an aging population with complex life course trajectories including divorce, separations, sole parenthood and longer stay of young adults in the parental home. Key emerging trends identified include: a more holistic approach to achieve resilient and sustainable communities and environments; inner-city infill is a priority area in large cities, with higher densities in bigger cities accommodating a broad variety of dwelling types; community engagement and input is increasingly considered as a valuable resource; and more resource efficient housing developments are needed and are becoming mandatory.